Rehabilitation Nursing and ventilatory weeaning in an Intensive Care Unit - Rui Miguel Outeiro; Salete Soares (Associação Portuguesa dos Enfermeiros de Reabilitação, 2021)
Introduction: Successful ventilatory weaning is essential, translating into a reduction in the length of stay in the Intensive Care Units (ICU), in the minimization of the sequelae of mechanical ventilation and in the maximization of the quality of life, where the Rehabilitation Nurse (ER) plays a key role. Methodology: Qualitative, descriptive, exploratory study. All ER (4) exercising functions in a UCI of ARS Norte participated. A semi-structured interview and systematic non-participated observation were used, after which a content analysis and crossing of data collected in the interviews and in the observation were carried out. The objective is to know the perception of RE in ventilatory weaning. Results: Motor and respiratory rehabilitation and the assessment of the person are interventions identified by the RE in the care of the person undergoing ventilatory weaning, which should be started early. The identified difficulties are related to the lack of material, absence of a ventilatory weaning protocol, lack of interaction between the team and deficit in the continuity of care Discussion: The intervention of the RE in the person undergoing ventilatory weaning translates into positive gains such as the minimization of immobility sequelae, increased muscle strength, training for autonomy and rapid ventilatory weaning. The development of a structured and systematized assessment instrument are key elements in this process Conclusion: Ventilatory weaning is a very specific process where the intervention of the RE requires the acquisition and development of very specific skills. The inclusion of these contents in specialized training, continuous training and in the recognition of experiences in similar realities is highlighted.